Factors influencing customer’s online purchase intention amongst Generation Z - Chong, Wan Sin; Lau, Hym-Fai; Ng, Ying Hui; Tan, Jia Rong; Wong, Yee Shuin (2022)
The rapid advancement of the Internet and social media in the current age of globalization not only developed a new means for people to communicate with others around the globe regardless of geographical distance and difference in time, but at the same time, a new form of commerce has emerged, which is so-called online shopping. According to studies regarding Malaysia online shopping, the online business in Malaysia has drastically become one of the largest markets in Southeast Asia. In today’s competitive online market, the marketers can no longer compete with others merely based on the price of their products or services. Factors from different perspectives should be identified by marketers to have a fruitful insight to satisfy customers’ demands. Thereby, this study seeks to fulfil the gap by examining the factors that influence consumers’ online purchase intention amongst Generation Z in the context of Malaysia. A conceptual framework is proposed by applying the Theory of Planned Behaviour (TPB). Five independent variables were employed in measuring customers’ online purchase intention, included brand recognition, perceived risks, peer pressure, electronic word of mouth (e-WOM), and perceived ease of use (PEOU). Quantitative method is used whereby a total of 396 questionnaires were distributed in Google Form to Malaysians aged between 11-26. Statistical Package for the Social Science (SPSS) was utilized to analyse the collected data. The results showed that all the proposed independent variables have positive and significant influences on customer’s online purchase intention amongst Generation Z. As a result, the ideas provided in the present study are beneficial to both online marketers and future academic researchers to have valuable understandings of the factors that influence customer’s online purchase intention amongst Generation Z in Malaysia.